PENINGKATAN KREATIVITAS PESERTA DIDIK KELAS VI PADA MATERI IPAS MELALUI MODEL PEMBELAJARAN PJBL DI SDN SAWOJAJAR 1 KOTA MALANG - Ahmad Abdul Wahid; Maharani Putri Kumalasani; Anik Dewi Lestari (STKIP Subang, 2023)
The educational process cannot be separated from a teaching and learning activity. There are two factors that make children less creative, namely internal factors (which come from within the students) and external factors (which come from the environment around the students). Focusing on the problems researchers will create learning strategies that can provide solutions and of course involve students actively, innovatively and creatively. Learning aims to increase the creativity of students. In the independent curriculum more emphasis on two learning models namely Project Based Learning (PJBL) and Problem Based Learning (PBL). In this regard, the professional competence of a teacher is needed, when choosing models, methods and learning media to achieve the expected learning objectives. The research model used by researchers in this study is the action research model class Kemmis and Mc Taggart. This research was conducted during II cycles with four interrelated stages in each cycle, namely: planning, action, observation, and finally reflection. The subjects of this study were students of class VI at SDN Sawojajar 1 Malang City for the 2022/2023 academic year, which consisted of 30 students. Consists of 12 male students and 18 female students. The object of this research is the creativity of students in the learning process. The results of product assessments produced by students showed that the ability to sketch pottery, the neatness of paint on pottery, the attitude of responsibility and discipline increased most significantly. The ability to sketch pottery is increased by 35%. The neatness of the paint on the pottery increased by 41%. Aspects of attitude of responsibility and discipline increased by 24%. The suitability of the material produced by students in both cycle I and cycle II all shows the achievement of learning objectives with the material being studied. The results of the analysis of the data obtained during the evaluation showed an increase in learning outcomes from cycle I to cycle II. From the classical percentage in cycle I, it showed that 22 out of 30 students completed or 73% percent fulfilled the KKM. In cycle II there was an increase from 30 students who completed to 28 students or 93% percent, only 2 students remained who had not fulfilled the KKM.